2022
DOI: 10.3390/catal12010049
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Properties of a BaTiO3/MWCNT Composite for Citric Acid Detection

Abstract: Although barium titanate (BaTiO3) shows prominent dielectric properties for fabricating electronic devices, its utilization in electrochemical applications is limited. Thus, this study examined the potential of a BaTiO3-based composite in the detection of a food additive, i.e., citric acid. First, a submicron-scale BaTiO3 powder was synthesized using the solution combustion method. Then, a BaTiO3/multiwalled carbon nanotube (MWCNT) composite was hydrothermally synthesized at BaTiO3:MWCNT mass ratios of 1:1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…The resulting images reveal irregular shapes, with the MWCNTs being fully covered, as reported previously [75]. It was also observed that an increase in the concentration of MWCNT led to its agglomeration [48].…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
See 1 more Smart Citation
“…The resulting images reveal irregular shapes, with the MWCNTs being fully covered, as reported previously [75]. It was also observed that an increase in the concentration of MWCNT led to its agglomeration [48].…”
Section: Scanning Electron Microscopysupporting
confidence: 81%
“…Furthermore, the XRD patterns of pure BaTiO3 and BaTiO3/MWCNT nanocomposites showed a weak peak (labeled with "*") at 24.16° and 24.61° that can be attributed to (111) and (102) reflection planes of BaCO3 (JCPDS N° 00-041-0373). This formation is associated with the result of a chemical reaction between barium from the starting reagent and citric acid during the combustion process [48]. The Rietveld refinement results indicate that the addition of 3% of MWCNT reduces the crystallite size of BaTiO 3 from 83.27 to 57.71 nm, compared to pure BaTiO 3 .…”
Section: X-ray Diffraction Resultsmentioning
confidence: 94%